Propriedades eletroquímicas de aços inoxidáveis 316L E 321 goivados com eletrodo de grafita e soldados por arco submerso - Campesan, Gabriel Roberto (2022)
In the maintenance and manufacturing practices of equipment in the petrochemical industry, the electric arc gouging procedure with graphite electrode is used in the preparation of carbon steel joints to be repaired or joined by the welding process. It is noted, however, that there is not much information in the literature about the magnitude of carbon contamination in stainless steels gouged with an electric arc by graphite electrode, and the consequences on the electrochemical properties. Welding standards, including N-133, Rev N from Petrobras, do not allow the use of this preparation technique for stainless steel, accepting the hypothesis that carbon contamination would be above the permissible, and it would compromise the mechanical properties and the corrosion resistance. Therefore, this project aims to evaluate the use of this process (gouging followed by welding) considering two types of austenitic stainless steels, AISI 316L and AISI 321, verifying the resulting gouging effect followed by welding on the electrochemical properties. The repaired/welded joints were studied in three different situations regarding the treatment of joint preparation after gouging, namely: i) without any type of cleaning, ii) brushing and iii) machining. Two types of joints were investigated, X and V, to simulate root pass preparation and defect repair, respectively. The degree of sensitization of the welded joint was evaluated using the double loop potentiokinetic reactivation technique (DL-EPR) according to ISO 12732 Corrosion of metals and alloys — Electrochemical potentiokinetic reactivation measurement using the double loop method (based on Cihal's method), and the susceptibility to intergranular corrosion according to ASTM A262-15 Standard Practices for Detecting Susceptibility to Intergranular Attack in Austenitic Stainless Steels, Practice A. The results showed that the air carbon arc gouging has no effect on the corrosion resistance of the studied alloys